2021
DOI: 10.1186/s13722-021-00251-9
|View full text |Cite
|
Sign up to set email alerts
|

Plausibility of patient-centred care in high-intensity methadone treatment: reflections of providers and patients

Abstract: Background Patients with opioid use disorder (OUD) often have complex health care needs. Methadone is one of the medications for opioid use disorder (MOUD) used in the management of OUDs. Highly restrictive methadone treatment—which requires patient compliance with many rules of care—often results in low retention, especially if there is inadequate support from healthcare providers (HCPs). Nevertheless, HCPs should strive to offer patient-centred care (PCC) as it is deemed the gold standard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(82 reference statements)
0
11
0
1
Order By: Relevance
“…They do, however, not suit all opioid dependent individuals, with an estimated 46% of the population not engaging with OST [ 23 , 24 ] and many maintaining illicit heroin use while in treatment [ 25 , 26 ]. Barriers such as limited accessibility, stigmatisation, and high-intensity treatment regimes can impede engagement and retention, leaving many individuals cycling in and out of treatment [ 23 , 24 , 27 ]. A significant population of opioid users remain in need of acceptable and accessible treatment options to address their increased risk of DRD, imprisonment, homelessness, and other health and social impacts related to illicit substance use [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…They do, however, not suit all opioid dependent individuals, with an estimated 46% of the population not engaging with OST [ 23 , 24 ] and many maintaining illicit heroin use while in treatment [ 25 , 26 ]. Barriers such as limited accessibility, stigmatisation, and high-intensity treatment regimes can impede engagement and retention, leaving many individuals cycling in and out of treatment [ 23 , 24 , 27 ]. A significant population of opioid users remain in need of acceptable and accessible treatment options to address their increased risk of DRD, imprisonment, homelessness, and other health and social impacts related to illicit substance use [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The attitudes and perspectives reflected across the public, treatment organizations, family, friends, and even others in recovery all shape the views of the individual struggling with OUD (Marshall, Maina, and Sherstobitof 2021; Pescosolido and Martin 2015). If community members, service providers, family and friends, and even those trying to manage recovery all hold up abstinence as the standard for health, those with OUD may be set up to fail.…”
Section: Discussionmentioning
confidence: 99%
“… 45 However, there are indications that clinics serving patients in OAT are less likely to use person-centered care than health care in general. 46 - 48 Recent studies have reported a lack of patient input into treatment decisions in OAT, which makes the patients feel under the control of the health care authority, rather than in own control. 49 This, in turn, may create conditions for poor outcomes with OAT.…”
Section: Discussionmentioning
confidence: 99%